Negotiation and groups - Mannix, Elizabeth A., 1960-; Neale, Margaret Ann; Overbeck, Jennifer R. (Emerald, 2011)
Negotiation is a process that permeates our everyday lives. From international conflicts to corporate mergers, from labor contracts to distribution agreements, and from one-time job offers to the day-to-day of relationships, negotiation is one of the most common ways to reach agreement on disputed issues and resources. Though negotiation is challenging in the simplest of circumstances, a group context can make it even more complex: groups negotiating with other groups may argue among themselves; factions and coalitions may develop, leading to side deals or the obstruction of deals in progress; the interests and preferences of all parties become much harder to identify, much less satisfy. In this fourteenth volume of the Research on Managing Groups and Teams series, nine chapters examine the particular challenges, opportunities, and dynamics that confront groups engaged in negotiation. The volume will be of particular interest to readers and scholars from management, psychology, sociology, communications, law, political science, and public policy.
Keywords: Negotiation in business.; Teams in the workplace -- Management.; elektronické knihy; electronic books